Pengaruh Current Ratio (CR) Dan Return On Assets (ROA) Terhadap Price Book Value (PBV) Pada Perusahaan Industri Makanan & Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 - Dava Indira Dandy; Wildan Fathil Padil; Alfiana Alfiana (Indo Publishing, 2026)
This study aims to analyze the effect of Current Ratio (CR) and Return on Assets (ROA) on Price to Book Value (PBV) in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The research method used is a quantitative approach with an associative research type. The data used are secondary data in the form of annual financial reports of companies obtained from the official IDX website and each company. The analysis technique used is panel data regression with a Random Effect Model (REM) estimated using the Generalized Least Square (GLS) method. The results show that partially Current Ratio (CR) has a negative and significant effect on Price to Book Value (PBV), while Return on Assets (ROA) has a positive and significant effect on PBV. Simultaneously, CR and ROA have a significant effect on PBV. The coefficient of determination value of 97.3% indicates that most of the variation in PBV can be explained by CR and ROA, while the remainder is influenced by other variables outside the research model. The results of this study indicate that profitability has a more dominant role than liquidity in determining company value.